Zelda and Ivy - Kvasnosky, Laura McGee (Cambridge, MA : Candlewick Press, 1998)
In three brief stories, Ivy, the younger of two fox sisters, submits to her older sister's schemes, even when they seem a bit daring.
Circus act -- The latest style -- Fairy dust.
Wilson's Children.
Elem. School Library Collection.
School Library Journal starred.
1.5
K-3
Keywords: Foxes -- Fiction; Sisters -- Fiction; Foxes -- Fiction; Sisters -- Fiction; Foxes -- Fiction; Sisters -- Fiction